Emergency department extracorporeal membrane oxygenation as a rescue therapy for ventricular tachycardia electrical storm: a case report - Andrew Pugh; Joseph E. Tonna; Scott Youngquist; John J. Ryan; Graham Brant‐Zawadzki (Journal of the American College of Emergency Physicians Open)
Abstract Arrhythmogenic right ventricular cardiomyopathy is a cause of sudden cardiac death in often otherwise healthy young adults. Cardiac arrest following an unstable tachydysrhythmia may be the primary presenting symptom. Venous arterial extracorporeal life support via extracorporeal membrane oxygenation (VA ECMO) has been used as a rescue strategy in emergency departments (EDs) for patients with cardiac arrest unresponsive to conventional cardiopulmonary resuscitation. We present a case of a previously healthy 18‐year‐old male who presented to our emergency department with ECG features of arrhythmogenic right ventricular cardiomyopathy and subsequent pulseless polymorphic ventricular tachycardia refractory cardiac arrest, treated with ED‐initiated VA ECMO.